The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1007/s42452-019-0195-z
|View full text |Cite
|
Sign up to set email alerts
|

Application of ANFIS and GRA for multi-objective optimization of optimal wire-EDM parameters while machining Ti–6Al–4V alloy

Abstract: The applications of artificial intelligence (AI) mainly, the hybrid approaches are becoming more popular and the relevant researches have been conducted in every field of engineering and science by using these AI techniques. Therefore, this research aims to examine the influence of wire electric-discharge machining parameters on performance parameters to improve the productivity with a higher surface finish of Titanium alloy (Ti-6Al-4V) by using the artificial intelligent technique. In this experimental analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 16 publications
0
15
0
1
Order By: Relevance
“…Higher the T ON , more is the surface roughness and material removal rate. Adaptive network based fuzzy inference system (ANFIS) model was developed by Sandeep et al [17] for multi objective optimization of surface roughness and material removal rate for machining titanium alloy with wire EDM and observed that T ON and IP are the most influencing parameters affecting the responses.…”
Section: Introductionmentioning
confidence: 99%
“…Higher the T ON , more is the surface roughness and material removal rate. Adaptive network based fuzzy inference system (ANFIS) model was developed by Sandeep et al [17] for multi objective optimization of surface roughness and material removal rate for machining titanium alloy with wire EDM and observed that T ON and IP are the most influencing parameters affecting the responses.…”
Section: Introductionmentioning
confidence: 99%
“…Comparative studies reveal that soft computing models provided the more accurate prediction in comparison with mathematical models. Kumar et al [24] in their experimental studies applied ANFIS techniques to develop the predictive model during wire EDM process. They analyzed the effect of process factor on responses through the developed model.…”
Section: Introductionmentioning
confidence: 99%
“…Manikandan et al (2017) investigated a multi-objective optimization using the Taguchi-gray method to enhance machining performance such as MRR and RA, overcut (OC) and perpendicularity error of electrochemical drilled Inconel 625. Kumar et al (2019) notice a significant improvement in MRR and RA using multi-optimization, namely, GRA and develop the ANFIS model for the predicted performance measure on WEDMed Ti–6Al–4V alloy.…”
Section: Introductionmentioning
confidence: 96%